2020
DOI: 10.1111/acv.12655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three techniques for genetic estimation of effective population size in a critically endangered parrot

Abstract: Understanding the current population size of small, spatially aggregating populations of species is essential for their conservation. Reliable estimates of the effective population size (Ne) can be used to provide an early warning for conservation managers of the risks to genetic viability of small populations. Critically endangered, migratory swift parrots Lathamus discolor exist in a single panmictic population in Australia. In their Tasmanian breeding range, they are at severe risk of predation by introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Allee effects likely exist in swift parrots and these are ignored in our models but are likely to exert a negative effect on population growth (Crates et al ., 2017). Further, we applied the most recent published population estimate in our contemporary model (Webb et al ., 2021), although ongoing genetic research suggests this value may be lower (Olah et al ., 2021). Finally, we ignore the effect of introduced nest competitors, such as starlings Sturnus vulgaris , which may reduce the carrying capacity of existing nesting areas (Stojanovic et al ., 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Allee effects likely exist in swift parrots and these are ignored in our models but are likely to exert a negative effect on population growth (Crates et al ., 2017). Further, we applied the most recent published population estimate in our contemporary model (Webb et al ., 2021), although ongoing genetic research suggests this value may be lower (Olah et al ., 2021). Finally, we ignore the effect of introduced nest competitors, such as starlings Sturnus vulgaris , which may reduce the carrying capacity of existing nesting areas (Stojanovic et al ., 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…After removing hybrid individuals, our results suggest LCT populations have concerningly low levels of genetic variation overall. Evaluation of the quantitative values of genomic metrics themselves, for comparison to other studies for example, is difficult given different filtering and analytical methods (De la Cruz & Raska, 2014; Diaz‐Arce & Rodriguez‐Ezpeleta, 2019), but effective population size is a transferable metric of genetic status (Antao et al, 2010; Carroll et al, 2018; Leroy et al, 2018) that can provide an early warning about genetic risks (Hohenlohe et al, 2021; Olah et al, 2021) and with guidance on minimum sizes necessary for ensuring persistence and evolutionary capacity (Frankham et al, 2014; Franklin, 1980; Traill et al, 2010). However, because it can be difficult to measure accurately with whole population sampling such as ours (Serbezov et al, 2012; Waples et al, 2014), recent studies have demonstrated the benefit of the cohort‐based metric effective number of breeders ( N b ) as potentially useful for gaging abundance (Ferchaud et al, 2016; Luikart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the island of Tasmania and its own offshore islands, a study of the migratory Swift Parrot Lathamus discolor could not detect genetic differentiation among breeding populations in consecutive years and across multiple islands [133]. Genetic estimations were used to calculate the effective population size of their single, panmictic population, and after combining it with demographic data, the study calculated a potential contemporary population size as low as 300 individuals [134].…”
Section: Conservation Genetics and Genomicsmentioning
confidence: 99%